Efforts to Implement the Local Content of the Sukamara Dialect Malay as a Medium for Revitalization and Conservation of Regional Languages - Misrita Misrita; Wahyudi Wahyudi; Agung Wibowo; Imam Qalyubi (Edumaspul: Jurnal Pendidikan, 2023)
The phenomenon of the condition of the Malay regional language of the Sukamara dialect (MDS) is currently a very dominant factor threatening the extinction of its people's identity. As a result of observations, the condition of language in Sukamara Regency is quite worrying because there is a phenomenon of linguistic shifts. Referring to the concerns in the description above, research related to the Sukamara Dialect Malay (BMDS) was carried out. This research uses a qualitative approach with phenomenological design to describe the phenomena that occur related to regional language shifts in Sukamara. From the observations made in this study, it was found that the vitality of the Sukamara Dialect Malay language (MDS) is in a moderate status, but if it is not done seriously, it will have an impact on extinction. In the domain analysis, it was found that MDS in the family domain is still actively used, especially in the native Sukamara family, while in migrant families it tends to use its native language. In other domains such as in Education, government offices, the language used depends on the opponent of speech and in what situation, as well as the use of language in public spaces is fluid, meaning it depends on the participants involved in the speech. Based on the results of the study above as a follow-up, namely the creation of local content of BMDS in schools as a response to linguistic conditions that if not anticipated will change the status of BMDS to critical or poor levels.